K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 12 2020

2x(3x - 5) - (5 - 3x) = 0

=> 2x(3x - 5) + (3x - 5) = 0

=> (3x - 5)(2x + 1) = 0

=> \(\orbr{\begin{cases}3x-5=0\\2x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=-\frac{1}{2}\end{cases}}\)

Vậy x \(\in\left\{\frac{5}{3};-\frac{1}{2}\right\}\)là giá trị cần tìm

10 tháng 12 2020

\(P=\frac{1}{x^2-x+1}+1-\frac{x^2+2}{x^3+1}\)

\(\Rightarrow P=\frac{1}{x^2-x+1}+1-\frac{x^2+2}{\left(x+1\right)\left(x^2-x+1\right)}\)

\(\Rightarrow P=\frac{1\left(x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}+\frac{1\left(x+1\right)\left(x^2-x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}-\frac{x^2+2}{\left(x+1\right)\left(x^2-x+1\right)}\)

\(\Rightarrow P=\frac{1\left(x+1\right)+1\left(x+1\right)\left(x^2-x+1\right)-x^2-2}{\left(x+1\right)\left(x^2-x+1\right)}\)

\(\Rightarrow P=\frac{x+1+1\left(x^3+1\right)-x^2-2}{\left(x+1\right)\left(x^2-x+1\right)}\)

\(\Rightarrow P=\frac{x+1+x^3+1-x^2-2}{\left(x+1\right)\left(x^2-x+1\right)}\)

\(\Rightarrow P=\frac{x+x^3-x^2}{\left(x+1\right)\left(x^2-x+1\right)}=\frac{x\left(1+x^2-x\right)}{\left(x+1\right)\left(x^2-x+1\right)}\)

\(\Rightarrow P=\frac{x\left(x^2-x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}=\frac{x}{x+1}\)

8 tháng 12 2020

a) x^2 - 2xy + y^2 - xz + yz 

= (x^2 - 2xy + y^2 ) - (xz + yz)

= (x - y)^2 - z(x + y)

= (x - y)(x - x + y)

8 tháng 12 2020

x2+y2_xy-3x+3=0

x2+y2-xy-3x=0-3=(-3)

x2+y2-xy=(-3):3=(-1)

x2+y2=(-1)+x.y

2x+y=

...............................................................CHỊU

P=x2010+y10

x:y thuoc 0

8 tháng 12 2020

\(\left(\frac{x}{xy-y^2}+\frac{2x-y}{xy-x^2}\right):\left(\frac{1}{x}+\frac{1}{y}\right)\)

\(=\left(\frac{x}{y\left(x-y\right)}-\frac{2x-y}{x\left(y-x\right)}\right):\left(\frac{y}{xy}-\frac{x}{xy}\right)\)

\(=\left(\frac{x}{y\left(x-y\right)}+\frac{2x-y}{x\left(x-y\right)}\right):\left(\frac{y-x}{xy}\right)\)

\(=\left(\frac{x^2}{xy\left(x-y\right)}+\frac{\left(2x-y\right)y}{xy\left(x-y\right)}\right):\left(\frac{y-x}{xy}\right)\)

\(=\frac{x^2+2xy-y^2}{xy\left(x-y\right)}.\frac{xy}{-\left(x-y\right)}=\frac{x^2+2xy-y^2}{-\left(x-y\right)}\)

8 tháng 12 2020

\(x^3+5x^2-4x-20=0\)

\(\Leftrightarrow x^2\left(x+5\right)-4\left(x+5\right)=0\)

\(\Leftrightarrow\left(x^2-4\right)\left(x+5\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(x+2\right)\left(x+5\right)=0\Leftrightarrow x=\pm2;-5\)